2020
DOI: 10.1029/2020gl088664
|View full text |Cite
|
Sign up to set email alerts
|

Tropical Rainfall Linked to Stronger Future ENSO‐NAO Teleconnection in CMIP5 Models

Abstract: The El Niño-Southern Oscillation (ENSO) has previously been shown to influence the winter North Atlantic Oscillation (NAO). Here we investigate the ENSO-NAO teleconnection in historical and RCP8.5 scenario CMIP5 simulations and show a future strengthening of the teleconnection under RCP8.5. The teleconnection strength is associated with increased East Pacific tropical rainfall variability. Stratospheric and tropospheric teleconnection pathways are examined, with both pathways having stronger links in the futur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 55 publications
6
20
0
Order By: Relevance
“…While a systematic study of the relative importance of each of these mechanisms is outside the scope of this study, Zhou et al (2020) suggest that the extension of the North Pacific jet with warming can explain shifts in MJO teleconnections over the western United States in CMIP5 and CMIP6 simulations. On seasonal timescales, Fereday et al (2020) also concluded that an extension of the Pacific and Atlantic jet-streams under RCP8.5 lead to a strengthening of the tropospheric pathway between the El Nino-Southern Oscillation and the NAO. We also find a robust extension of the North Pacific and North Atlantic jet-streams within CESM2-WACCM (contours in Figure 2c).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…While a systematic study of the relative importance of each of these mechanisms is outside the scope of this study, Zhou et al (2020) suggest that the extension of the North Pacific jet with warming can explain shifts in MJO teleconnections over the western United States in CMIP5 and CMIP6 simulations. On seasonal timescales, Fereday et al (2020) also concluded that an extension of the Pacific and Atlantic jet-streams under RCP8.5 lead to a strengthening of the tropospheric pathway between the El Nino-Southern Oscillation and the NAO. We also find a robust extension of the North Pacific and North Atlantic jet-streams within CESM2-WACCM (contours in Figure 2c).…”
Section: Resultsmentioning
confidence: 96%
“…On seasonal timescales, Fereday et al. (2020) also concluded that an extension of the Pacific and Atlantic jet‐streams under RCP8.5 lead to a strengthening of the tropospheric pathway between the El Nino‐Southern Oscillation and the NAO. We also find a robust extension of the North Pacific and North Atlantic jet‐streams within CESM2‐WACCM (contours in Figure 2c).…”
Section: Resultsmentioning
confidence: 99%
“…Fereday et al. (2020) have recently argued that tropical rainfall will also have an increasing dynamic impact on extratropical climate, meaning that an understanding of tropical rainfall dynamics is essential for both near‐term predictability and longer‐term climate projections on increasingly large spatial scales. We therefore consider these process‐based assessments of rainfall projections to be essential for other parts of the tropics, and they must be used for the new CMIP6 model generation.…”
Section: Discussionmentioning
confidence: 99%
“…The general pattern of omega decrease to the north of the domain and increase to the south is suggestive of a northward shift of the zone of maximum tropical convergence (Creese, Washington, & Jones 2019;Creese, Washington, & Munday, 2019). Fereday et al (2020) have recently argued that tropical rainfall will also have an increasing dynamic impact on extratropical climate, meaning that an understanding of tropical rainfall dynamics is essential for both near-term predictability and longer-term climate projections on increasingly large spatial scales. We therefore consider these process-based assessments of rainfall projections to be essential for other parts of the tropics, and they must be used for the new CMIP6 model generation.…”
Section: 1029/2021jd034585mentioning
confidence: 99%
See 1 more Smart Citation